Long-term sport development in portuguese futsal players - Serrano, J.; Shahidian, S.; Leite, N. (International Journal of Sports Science, 2014)
Characterization of long-term athlete development of experts is a process that could identify the underlying mechanisms of excellence in sports and define the patterns that make it possible to reformulate the dynamic process of talent identification. The objective of the study was to identify differences in the long-term athlete development in three competitive levels of futsal players: expert, intermediate and non-expert. The participants filled out a questionnaire, based on retrospective information. The results showed significant differences among all competitive levels in the futsal starting age, in the inactivity period between seasons and in the time spent in training activities.